1996
DOI: 10.1103/physrevlett.77.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Free Surfaces on the Glass Transition Temperature of Thin Polymer Films

Abstract: We report the first measurements of the glass transition temperature T g for thin freely standing polystyrene (PS) films. We have used Brillouin light scattering to measure T g for freely standing films of different thicknesses. We find that T g decreases linearly with film thickness h for h # 700 Å, with a reduction of 70 K for a film with h 290 Å. These measurements characterize unambiguously the effects of the free surface on T g of thin polymer films. Results are compared to similar results for supported P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

57
847
8
5

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,087 publications
(939 citation statements)
references
References 15 publications
57
847
8
5
Order By: Relevance
“…8,27,28 Moreover, the idea of a bilayered structure of spin-coated films is also often used to explain the thickness dependence of the glass transition temperature in conjugated polymers. 6,7 Here, we report spectroscopic evidence of the bilayered structure of a thin polymer film, which confirms the exciton quenching effect in the skin layer.…”
Section: Resultssupporting
confidence: 76%
“…8,27,28 Moreover, the idea of a bilayered structure of spin-coated films is also often used to explain the thickness dependence of the glass transition temperature in conjugated polymers. 6,7 Here, we report spectroscopic evidence of the bilayered structure of a thin polymer film, which confirms the exciton quenching effect in the skin layer.…”
Section: Resultssupporting
confidence: 76%
“…These differences have implications for the properties of such materials confined on the nanometer length scale. For example, the glass transition temperature (T g ) of amorphous polymer thin films has been observed either to increase or decrease with decreasing film thickness, [16][17][18][19][20][21][22][23][24][25][26][27][28] phenomena that have attracted great interest in recent years as part of a larger effort to understand the nature of the glass transition itself. The first systematic study of the dependence of the T g on film thickness in thin polymer films was performed by Keddie et al using ellipsometry.…”
Section: Introductionmentioning
confidence: 99%
“…24 This interfacial control of physical properties is also demonstrated by the greater decrease in T g observed for free-standing thin films, compared to films adhered to some substrates. [25][26][27][28] Numerous simulation studies have been conducted to reveal the underlying mechanism of the glass transition in spatially confined polymers. Torres et al have demonstrated in MD simulations that the diffusivity of polymer segments is highly heterogeneous in polymer thin films, and that it is strongly correlated with deviations of T g from the bulk.…”
Section: Introductionmentioning
confidence: 99%
“…Both sound velocities (c l , c t ) are sensitive index of T g , [36,49,110,111] due to the rapid increase of compressibility (C −1 11 ) and decrease of shear rigidity (C 44 ). Hence, tracking the frequency of a distinct vibration mode (Eq.…”
Section: Elastic Vibrations In Nanostructered Colloidsmentioning
confidence: 99%
“…Enhanced dynamics at the surface of amorphous materials allows for rapid configurational sampling in the top few nanometers. [110,111,[171][172][173] Vapor deposition can build an efficiently packed amorphous material in a layer-by-layer fashion by taking advantage of the enhanced surface dynamics and thus is not limited by the slow relaxation dynamics of the bulk. [31] The mechanical properties of vapor-deposited films are determined using Brillouin light scattering spectroscopy (BLS).…”
Section: Bls Experiments On Imcmentioning
confidence: 99%